DO YOUTUBE SOCIAL MEDIA SHOWS AFFECT THE POLITE OF ELEMENTARY SCHOOL STUDENTS? - Bubun Burhanudin; Yayan Alpian; Sinta Maria Dewi (Universitas Majalengka, 2024)
Along with developments in the current era of communication technology, the use of gadgets has penetrated into elementary school-age students, this has caused many concerning phenomena that have an impact on the behavior and speech that children imitate, one of the phenomena caused by content on YouTube social media is related to manners, such as following speech that is not politely spoken. The study aims to describe the influence of YouTube social media impressions that occur in elementary schools in East Karawang District, Karawang Regency using a descriptive qualitative approach research method. Data collection techniques were carried out using observation interviews with field note techniques and questionnaires. The results of this study found that students behave disrespectfully, especially in terms of speech, namely rude speech obtained from watching YouTube social media content that is not good. But on the other hand, the results of this study were found from watching positive YouTube social media, namely content that inspires students to do good such as conducting social donation activities to people in need. Thus, the influence of YouTube social media broadcasts on students' polite behavior is quite influential.